Superior gluteal nerve: a new block on the block? - Sá,Miguel (2018)
Abstract Background and objectives The superior gluteal nerve is responsible for innervating the gluteus medius, gluteus minimus and tensor fascia latae muscles, all of which can be injured during surgical procedures. We describe an ultrasound-guided approach to block the superior gluteal nerve which allowed us to provide efficient analgesia and anesthesia for two orthopedic procedures, in a patient who had significant risk factors for neuraxial techniques and deep peripheral nerve blocks. Clinical report An 84-year-old female whose regular use of clopidogrel contraindicated neuraxial techniques or deep peripheral nerve blocks presented for urgent bipolar hemiarthroplasty in our hospital. Taking into consideration the surgical approach chosen by the orthopedic team, we set to use a combination of general anesthesia and superficial peripheral nerve blocks (femoral, lateral cutaneous of thigh and superior gluteal nerve) for the procedure. A month and a half post-discharge the patient was re-admitted for debriding and correction of suture dehiscence; we performed the same blocks and light sedation. She remained comfortable in both cases, and reported no pain in the post-operative period. Conclusions Deep understanding of anatomy and innervation empowers anesthesiologists to solve potentially complex cases with safer, albeit creative, approaches. The relevance of this block in this case arises from its innervation of the gluteus medius muscle and posterolateral portion of the hip joint. To the best of our knowledge, this is the first report of an ultrasound-guided superior gluteal nerve block with an analgesic and anesthetic goal, which was successfully achieved.